Different natures: an ecocritical analysis of selected films by Terrence Malick, Werner Herzog and Sean Penn - Van Wyk, Karl (My University, 2012)
Humanity’s relationship with nature has, in recent years, undoubtedly been one of contention and turmoil, an issue whose drama is gaining popularity in popular culture and, especially, film. In this dissertation I examine how these challenging human-nature relationships play out in Terrence Malick’s The New World, Werner Herzog’s Grizzly Man and Encounters at the End of the World, Sean Penn’s Into the Wild, and the Jon Krakauer book, of the same title, upon which Penn’s film is based. As one’s views on nature (like all else) are mediated through language, using ecocritical principles slanted towards filmic, as opposed to written, texts, I provide a close examination of the ways in which these artists portray the relationship between language and nature, and the impact this has on our cultural and individual identities. I will also show how these primary texts make use of centuries-old Romantic aesthetics in order to humanise nature for moral ends. The primary texts agree that a large part of the problem in the poor relationship between humanity and nature is due to inadequate metaphors with which humanity views the earth. Thus, each artist promotes a certain kind of anthropomorphic understanding of nature which he believes is pivotal in encouraging better interconnections between humanity and nature. As a result, I provide a critique of the kinds of metaphors used by each respective artist, where some metaphors of nature may support or contradict a certain artist’s aims in his portrayal of human-nature relationships.
M.A. University of the Witwatersrand, Faculty of Humanities, 2012.
Keywords: Terrence Malick; Werner Herzog; Sean Penn; Jon Krakauer; nature; film; documentury; ecocriticism; celluloid ecocriticism; ecofeminism; deep ecology; anthropocentrism; anthropomorphism; Romanticism; Gaia